Local government perspectives on decentralization [videorecording] - Asian Development Bank.; Ateneo Center for Social Policy and Public Affairs; Ford Foundation (Quezon City CSP/JCF, 1997)
Discusses current issues in decentralization as experienced in the municipalities, cities, and provinces. Presented during a workshop-seminar for the Asian Development Bank on April 1997.
VHS.
Host, Lia Andonai; editor, Jovy Masing II.
Keywords: Decentralization in government -- Philippines; Rural development projects -- Management. -- Philippines; Central-local government relations -- Philippines; POLITICAL SCIENCE; SOCIAL SCIENCE